Requirements for PKC-augmented JNK activation by MKK4/7 - Lopez Bergami, Pablo Roberto (2008)
The c-Jun N-terminal kinases (JNKs) are activated in response to stress, DNA damage, and cytokines by MKK4 and MKK7. We recently demonstrated that PKC can augment the degree of JNK activation by phosphorylating JNK, which requires the adaptor protein RACK1. Here we report on the conditions required for PKC-dependent JNK activation. In vitro kinase assays reveal that PKC phosphorylation of JNK is not sufficient for its activation but rather augments JNK activation by canonical JNK upstream kinases MKK4 or MKK7 alone or in combination. Further, to enhance JNK activity, PKC phosphorylation of JNK should precede its phosphorylation by MKK4/7. Inhibition of PKC phosphorylation of JNK affects both early and late phases of JNK activation following UV-irradiation and reduces the apoptotic response mediated by JNK. These data provide important insight into the requirements for PKC activation of JNK signaling.